Efficiency of Raw Material Steel Inventories in Improving Supply Chain Performance at Honda Trading Indonesia - Gigih Hapsak Pradipto; Ahmad Lussy (JURNAL TEKNIK INDUSTRI, 2019)
The production and number of processed automotive industries have slightly increased; as a result, the companies must compete to maximize their profits by conducting their efficient production process. PT. Honda Trading Indonesia is belong to Honda Motor group company, especially in support import material such as Raw Material and Parts that has implemented supply chain management. It is necessary for the company to take measurements of its performance and efficiency for the entire supply chain such as procurement of raw materials. The purposes of this study were to analyze the performance of the company's supply chain and determine the most efficient method of procurement for its raw materials as well as and to provide recommendations for the company to improve its performance of entire supply chain. This study used SCOR in analyzing the performance of supply chain and EOQ and POQ method to be compared with the method that the company uses to determine which method of procurement for raw materials is the most efficient one. The result showed that based on the matrix, the company's performance is unfavorable when it was compared to the benchmark performance of inventory days of supply.